2022
DOI: 10.21037/gs-22-254
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: diagnostic value of different ultrasound for benign and malignant thyroid nodules

Abstract: Background: Conventional ultrasound and contrast-enhanced ultrasound (CEUS) are commonly used in the diagnosis of benign and malignant thyroid nodules. However, the value of the two methods in the diagnosis of benign and malignant thyroid nodules remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In our study group, the presence of the ring-enhancement feature was reported in 16.9% of benign lesions compared to 4.1% of thyroid carcinomas (p = 0.006), while univariate and multivariate logistic regression models did not distinguish this feature as significantly excluding the malignant nature of the lesion. Remaining in the group of benign lesions, the authors of the current study showed that the features of high enhancement and homogenous enhancement allow a significant differentiation of these lesions from thyroid carcinomas, which was also confirmed in numerous studies carried out with a larger number of patients [38].…”
Section: The Utility Of Ceus Patterns Assessed In the Study In Line W...supporting
confidence: 82%
“…In our study group, the presence of the ring-enhancement feature was reported in 16.9% of benign lesions compared to 4.1% of thyroid carcinomas (p = 0.006), while univariate and multivariate logistic regression models did not distinguish this feature as significantly excluding the malignant nature of the lesion. Remaining in the group of benign lesions, the authors of the current study showed that the features of high enhancement and homogenous enhancement allow a significant differentiation of these lesions from thyroid carcinomas, which was also confirmed in numerous studies carried out with a larger number of patients [38].…”
Section: The Utility Of Ceus Patterns Assessed In the Study In Line W...supporting
confidence: 82%
“…The pathological basis may be related to the malignant nodules’ complex neovascularization. Once the tumor grows beyond the newly formed vasculature, necrosis and embolism may occur in the tumor, resulting in an uneven enhancement or low enhancement pattern ( 5 , 12 , 32 ). Combining CEUS and quantitative analysis, our results also showed that malignant thyroid nodules tend to have low enhancement or uneven enhancement but without statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] In a recent meta-analysis, the sensitivity of CEUS was found slightly higher than that of conventional US in distinguishing between benign and malignant nodules (0.87; [95% CI: 0.82–0.90] vs. 0.84 [95% CI: 0.75–0.90]). [ 57 ] The perfusion type of CEUS has good diagnostic performance for cervical lymph node metastasis in PTC. [ 58 ]…”
Section: Imaging Methodsmentioning
confidence: 99%